A DFT Study of the Geometrical, Electronic, Optical, Spectroscopic and Wave Function Analyses (ESP, ELF, LOL) of 8-Hydroxy Coumarin: A Molecule with Large Medicinal Applications - Khatua, Sabyasachi (Journal of Scientific Research, 2026)
A comprehensive theoretical investigation of 8-hydroxy coumarin has been conducted to elucidate its geometrical, spectroscopic, and electronic properties. Geometrical analysis reveals the impact of the carbonyl and hydroxyl groups on bond lengths and bond angles. This is supported by consistent findings from Laplacian of electron density (∇²ρ) calculations. Natural Bond Orbital (NBO) analysis highlights significant conjugative and hyper-conjugative interactions that enhance molecular stability. Time-Dependent Density Functional Theory (TD-DFT) calculations identify a HOMO-LUMO energy gap of 4.32 eV, while simulated UV spectra feature sharp peaks at 220 nm and 289 nm, along with a small shoulder between 215–240 nm. Simulated Infrared (IR) and Nuclear Magnetic Resonance (NMR) spectra align well with experimental data. The electronic structure of 8-OH coumarin is explored through Electron Localization Function (ELF) and Localized Orbital Locator (LOL) studies. Density of States (DOS) studies unveils bonding, non-bonding, and antibonding interactions. Nonlinear optical (NLO) analysis reveals significant optical activity, while Reduced Density Gradient (RDG) analysis excludes intramolecular hydrogen bonding but indicates weak van der Waals and steric interactions.